Perjanjian perkawinan menurut perundang-undangan di Indonesia - Hannan, Abd.; Herlina , Herlina (Prodi Hukum Keluarga Islam Fakultas Syari'ah Universitas Islam Zainul Hasan Genggong Probolinggo, 2024)
This research is motivated by an explanation of marriage with the laws in Indonesia that discuss marriage agreements. According to imam shafi'i if a man marries a girl or widow by ordering a dowry of one thousand on condition that the wife may leave the husband's house whenever she wants or on condition that the husband may not take her out of his country or on condition that the husband may not mix her with another woman. If the marriage has already taken place, then the husband may do so and not fulfill the condition again, then the marriage remains valid but the condition is void. Meanwhile, the marriage agreement according to Indonesian law does not only regulate property issues and the consequences of marriage but also the rights and obligations of both parties as long as the agreement does not conflict with the limits of the law. Marriage is a permanent relationship between two people that is recognized as legitimate by the community concerned based on the applicable marriage regulations. Depending on the local culture, the form of marriage can vary and its purpose can vary as well. But generally marriage is exclusive and recognizes the concept of infidelity as a violation of marriage. This research was conducted to examine marital agreements in the perspective of Indonesian law. This research is conducted with a normative approach to analysis using primary and secondary materials presented qualitatively using the deductive method to get conclusions. The result of this study is that the juridical marriage agreement of the existence of the marriage agreement is that it does not cancel the existing marriage contract. The conclusion is that based on the descriptions described thoroughly, this research can be concluded that the marriage agreement made by the prospective husband and the prospective wife at the time or before the marriage is held which is legalized by the marriage registrar as regulated in Law number 1 of 1974 Article 29, emphasizes that the contents of the agreement must not violate the boundaries of law, religion and decency, meaning that it can be about anything.